Improving phosphorus utilization and iron homeostasis in maize through nitrification inhibitors and plant growth-promoting bacterium - Malakshahi Kurdestani, Ali; Ruser, Reiner; Nkebiwe, Peteh Mehdi; Chen, Xinping; Müller, Torsten (Frontiers in Agronomy, 2026)
IntroductionThis study aimed to investigate the effects of nitrification inhibitors (NIs), specifically DMPP (Dimethyl pyrazole phosphate) and DMPFA (Dimethyl pyrazole fulvic acid), and plant growth-promoting microorganisms (PGPM) on nutrient uptake, allocation, and plant growth in maize under low phosphorus (P) availability. The research questions explored whether NIs enhance P, manganese (Mn), and zinc (Zn) uptake through rhizosphere acidification, alter nutrient partitioning between roots and shoots, and whether DMPFA-PGPM combinations synergistically improve plant growth and nutrient acquisition.MethodsTwo rhizobox experiments were conducted using silt loam soil with low P content (8.7 mg kg−1 P-CAL, pH 6.4).ResultsIn the first experiment, maize was subjected to ten treatments, including ammonium (NH4 +) and nitrate (NO3 −) with or without DMPP, DMPFA, and rock phosphate (RP), compared to controls. The second experiment tested five treatments, including NH4 + with DMPFA, fulvic acid, and Bacillus atrophaeus (ABi05) as PGPM. Measurements included rhizosphere pH, acid/alkaline phosphatase activity, root exudates, phytohormones, root morphology, plant biomass, and nutrient (P, Mn, Zn, Fe, Ca, Mg, K) concentrations in shoots and roots. Nutrient use efficiencies (PUE, PFPp, NRE) were calculated, and data were analyzed using one-way ANOVA with Fisher’s LSD test (p<0.05). In the first experiment, DMPP+RP and DMPFA+RP treatments increased biomass by 31.8% and 38.5%, respectively, compared to the negative control, with total root length rising by up to 169.5% in the positive control (NO3 −+soluble P). Shoot Fe content was 60% higher in NI treatments, with Mn and Zn shoot concentrations increasing by up to 40.4% and 32.8%, respectively, in DMPFA treatments. The rhizosphere pH dropped by 0.5 units in NI treatments, thereby enhancing acid phosphatase activity. In the second experiment, DMPFA and DMPFA+ABi05 increased shoot biomass by 47.5% and 50.7%, respectively, and shoot P content by 45.1% and 62.7%. PUE was 56.2% higher with DMPFA+ABi05, and zeatin concentrations rose by 79.1% compared to controls.ConclusionDMP-based NIs significantly enhance P, Mn, and Zn uptake in maize by acidifying the rhizosphere and increasing nutrient solubility. NIs shift mainly Fe and Mn allocation toward shoots, improving nutrient mobilization. The synergistic effect of DMPFA and PGPM (ABi05) further boosts PUE and Zeatin.